2020
DOI: 10.1101/2020.08.26.267849
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Scanning ion conductance microscopy reveals differences in the ionic environments of gram positive and negative bacteria

Abstract: This paper reports on the use of scanning ion conductance microscopy (SICM) to locally map the ionic properties and charge environment of two live bacterial strains: the gramnegative Escherichia coli and the gram-positive Bacillus subtilis. SICM results find heterogeneities across the bacterial surface, and significant differences among the grampositive and -negative bacteria. The bioelectrical environment of the B. subtilis was found to be considerably more negatively charged compared to E. coli. SICM measure… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Some of the collective dynamics allow swarming bacteria to better cope with environmental stress. In a recent study, we showed that swarming B. subtilis colony can undergo biofilm formation through dynamic localised phase transition, which allows swarming bacteria to overcome several forms of environmental stress such as antibiotics, UV light and spatial confinement [52]. This phase transition appeared to be compatible with a physical theory of collective motion, known as motility-induced phase separation (MIPS), where self-propelled particles (e.g.…”
Section: Swarmmentioning
confidence: 55%
See 1 more Smart Citation
“…Some of the collective dynamics allow swarming bacteria to better cope with environmental stress. In a recent study, we showed that swarming B. subtilis colony can undergo biofilm formation through dynamic localised phase transition, which allows swarming bacteria to overcome several forms of environmental stress such as antibiotics, UV light and spatial confinement [52]. This phase transition appeared to be compatible with a physical theory of collective motion, known as motility-induced phase separation (MIPS), where self-propelled particles (e.g.…”
Section: Swarmmentioning
confidence: 55%
“…In the case of biofilm formation at solid-liquid interfaces, adhesion is the initial step, which is a complex process involving various physico-chemical factors and is mediated by van-der-Waals and electrostatic interactions between cells and surfaces [40,41]. Positively charged surfaces, which can result from the coating by positively charged compounds such as poly-L-lysis and APTES, promote the cell adhesion due to the fact that cellular surfaces are negatively charged [42]. Cell attachment can also be enhanced by decreasing hydrodynamic shear forces, hence local flow fields influence the attachment [43,44].…”
Section: Mechanical Surface Wavesmentioning
confidence: 99%
“…It has been reported that the bioelectrical environment of the Gram-positive bacteria is significantly more negatively charged than that of the Gram-negative bacteria. 48 Moreover, the result of the ζ-potential indicates that N,Cl-CDs have a positive charge. Therefore, there is an attractive force (positive and negative charges) between the Gram-positive bacteria and N,Cl-CDs, resulting in an allowance for more N,Cl-CD attachment to the Gram-positive bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…In an effort to improve the repertoire of tools used to study ion fluxes in living bacteria, researchers have used scanning ion conductance microscopy (SICM) to characterize the properties of the outer environment of the Gram-positive B. subtilis and the Gram-negative E. coli. 248 Both bacteria types have a negative surface charge, but data revealed a heterogeneous charge distribution and considerable differences between the two bacteria types, with an estimated net charge of −350 and −450 mC m −2 for B. subtilis and −80 to −140 mC m −2 for E. coli. However, more data will be needed to evaluate the origin and role of local charge distribution across cell types.…”
Section: Microbial Bioelectrochemical Techniquesmentioning
confidence: 94%